2018
DOI: 10.1111/pbr.12588
|View full text |Cite
|
Sign up to set email alerts
|

Higher grain yield and higher grain protein deviation underline the potential of hybrid wheat for a sustainable agriculture

Abstract: Grain yield and protein content are traits of major importance in wheat breeding, but their combination is challenging due to a tight negative correlation. Protein yield and grain protein deviation have been proposed as selection criteria to simultaneously improve both traits. Sedimentation volume is an indicator of protein quality, which plays an important role for bread-making quality in wheat. All these traits have been investigated in our study with 135 parental inbred lines, their 1,604 hybrids and 10 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
56
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 24 publications
9
56
2
Order By: Relevance
“…Based on three different models, our genome-wide prediction accuracy results suggest that genetic gains can be improved with high confidence. Our results are in line with the recent reports, where similar genome-wide prediction accuracies for quality traits were reported on wheat panels comprising of different genetic natures 12 , 20 , 42 , 43 , 63 . This warrants the efficient use of genomic selection in elite breeding programs to predict the total genetic merit of individuals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Based on three different models, our genome-wide prediction accuracy results suggest that genetic gains can be improved with high confidence. Our results are in line with the recent reports, where similar genome-wide prediction accuracies for quality traits were reported on wheat panels comprising of different genetic natures 12 , 20 , 42 , 43 , 63 . This warrants the efficient use of genomic selection in elite breeding programs to predict the total genetic merit of individuals.…”
Section: Discussionsupporting
confidence: 93%
“…Since most of the wheat quality parameters harbor a quantitative genetic architecture, genome-wide prediction—based on high-density molecular markers—to predict the total genetic value of a trait becomes a method of choice in applied breeding programs 41 . Recently, genome-wide prediction on wheat populations of diverse genetic backgrounds suggested that wheat quality traits can be predicted with high accuracy 12 , 20 , 21 , 42 , 43 .…”
Section: Introductionmentioning
confidence: 99%
“…Potential causes for this relationship are a dilution effect of nitrogen allocated to an increasing number of kernels conferring higher grain yields (Acreche and Slafer 2009 ) as well as the competition between carbon and nitrogen for energy (Munier-Jolain and Salon 2005 ). Although a strong negative genetic correlation is frequently observed between grain yield and protein content in wheat (Laidig et al 2017 ; Thorwarth et al 2018 ), environmental influences can extensively alter the magnitude of this negative relationship (Oury and Godin 2007 ) making it necessary to test genotypes in multi-environment trial networks to enable a simultaneous selection of both traits (Oury et al 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that selecting genotypes that show superior performance in the genomic selection index based on grain protein deviations potentially enables an indirect selection for a difficult to phenotype trait, which might lead to an indirect genetic improvement for this important component of nitrogen-use efficiency in a genomic breeding approach. The underlying genetic base of these deviations from the regression line is furthermore highlighted by a larger grain protein deviation of hybrid wheat in comparison with line varieties (Thorwarth et al 2018 ) that might also be influenced by a different root architecture to improve nitrogen uptake (Cormier et al 2016 ; Hawkesford 2017 ) and supposedly causes a larger yield stability for some genotypes (Mühleisen et al 2014 ; Liu et al 2017 ). Accordingly, several QTL related to grain protein deviation have been mapped in wheat amongst others in the proximity of major genes like Ppd - D1 regulating photoperiodic sensitivity and the semi-dwarfing genes Rht - B1 and Rht - D1 (Cormier et al 2014 ; Guttieri et al 2017 ) with some candidate genes being identified (Habash et al 2007 ; Li et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study assessed the potential of a large set of experimental modern wheat hybrids compared to their parents and check cultivars for grain yield, grain protein content, grain N deviation, and baking quality (Thorwarth et al, 2018). When analyzed by quality classes, hybrids showed often higher grain yield than line genotypes and check cultivars but lower protein content, whereas sedimentation volume as an indicator of baking quality was at similar levels.…”
Section: Introductionmentioning
confidence: 99%